Valve morphology of three species of Neidiomorpha (Bacillariophyceae) from Zoigê Wetland, China, including description of Neidiomorpha sichuaniana nov. sp. - Liu, Qi; Kociolek, J. P.; Wang, Quanxi; Fu, Chengxin (Phytotaxa, 2014)
A new diatom species, Neidiomorpha sichuaniana sp. nov., is described from Zoigê Wetland, China. The morphology of N. sichuaniana is documented by light and scanning electron microscope and discussed in detail, including a comparison with the two other species in the genus Neidiomorpha also found in Zoigê. Neidiomorpha sichuaniana has a smaller central area and smaller central constriction than N. binodiformis and less apiculate ends than N. binodis. We comment on the systematic position of Neidiomorpha based on the morphology of these three species.